On the semiclassical character of orthogonal polynomials satisfying structure relations - Branquinho, A. (2020)
Submitted by REBOCHO (mneves@ubi.pt) on 2020-02-03T13:29:44Z No. of bitstreams: 1 preprint DMUC structure OPRL.pdf: 261134 bytes, checksum: 39720dc385b41d0897cd83a46a4d2352 (MD5)